2018
DOI: 10.1039/c7sc04383j
|View full text |Cite
|
Sign up to set email alerts
|

Total chemical synthesis of glycocin F and analogues: S-glycosylation confers improved antimicrobial activity

Abstract: Replacing the O-linked saccharide in the bacteriocin glycocin F with an S-linked version results in a peptidomimetic that increases the bacteriostatic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…11,12 Its activity can be counteracted by adding GlcNAc to the growth medium, but not other sugars, 11 and recent studies showed that it is the GlcNAc on the interhelical loop that appears responsible for its activity. 13,14 A main difference in addition to glycocin F carrying two GlcNAc and sublancin only one Glc is that glycocin F is bacteriostatic, and sublancin is bactericidal. 8,11 Glycocin F is thought to interact with the GlcNAc PTS through a currently unknown mechanism with the C-terminal GlcNAc possibly responsible for its specificity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Its activity can be counteracted by adding GlcNAc to the growth medium, but not other sugars, 11 and recent studies showed that it is the GlcNAc on the interhelical loop that appears responsible for its activity. 13,14 A main difference in addition to glycocin F carrying two GlcNAc and sublancin only one Glc is that glycocin F is bacteriostatic, and sublancin is bactericidal. 8,11 Glycocin F is thought to interact with the GlcNAc PTS through a currently unknown mechanism with the C-terminal GlcNAc possibly responsible for its specificity.…”
Section: Resultsmentioning
confidence: 99%
“…Radioactivity was then determined on a scintillation counter (PerkinElmer Tri-Carb 2910 TR). The radiolabels and their corresponding positive and negative antibiotic controls were: Cell wall: [ 14 The procedure was the same as that listed above, except two concentrations (0.1% and 0.01%) of glucose were added in the refined LB medium to grow B. subtilis 168 ΔSPβ. A final concentration of 0.8 μCi/mL [ 14 C]-glucose (PerkinElmer, NEC042X050UC) was added.…”
Section: Macromolecular Synthesis Assaysmentioning
confidence: 99%
“…The sactibiotic subtilosin A displays rare sulphur to α-carbon bonds involving D-amino acid residues [46] and also has a head-to-tail cyclic backbone. Finally, glycocins are disulfide-bridged peptides that have sugar moieties linked to an additional cysteine residue, which are important for their antimicrobial activity [47]. The structure of sublancin 168 exhibits two α-helical segments that are linked by two disulfide bonds.…”
Section: Insert Boxmentioning
confidence: 99%
“…As a representative example, in 2018, Amso et al. reported the total synthesis of glycocin F (GccF; 14 ), which is a diglycosylated 43‐residue compound that contains two disulfide bridges between the residues Cys 5 –Cys 28 and Cys 12 –Cys 21 , forming two macrocycles . Total synthesis was achieved by using a native chemical ligation strategy .…”
Section: Bacterial Antimicrobial Cyclopeptidesmentioning
confidence: 99%
“…As ar epresentative example, in 2018, Amso et al reported the total synthesis of glycocin F ( GccF; 14), which is ad iglycosylated 43-residue compound that containst wo disulfide bridges between the residues Cys 5 -Cys 28 and Cys 12 -Cys 21 ,form-ing two macrocycles. [152] To tal synthesis was achieved by using an ative chemicall igation strategy. [153] The fully deprotected linear precursor was oxidized under optimal conditions by using 2mm cysteine, 0.25 mm cystine, and 0.1 mm EDTA in 1.5 m guanidine hydrochloride (Gn·HCl;p H8.2) at 4 8Cf or 16 h to afford the cyclized glycocin F(Scheme 4).…”
Section: Wwwchemmedchemorgmentioning
confidence: 99%